Conflict and Harmony between Islam and Local Culture in Reyog Ponorogo Art Preservation - Riyadi, M. Irfan; Mujahidin, Anwar; Tasrif, Muh. (UIN Maulana Malik Ibrahim Malang, 2016)
Reyog as performing art procession already existing in Ponorogo since pre-Islamic era still grows today even expanding outside the region of Ponorogo both regionally, nationally, and internationally. Reyog at the present time is generally acknowledged as cultural identity of Indonesian nation. The case is different with other Javanese traditions such as kentrung, ludruk, and ketoprak that has collapsed over time. This fact raises interesting questions of how Reyog could withstand against the onslaught of various cultures that come to attack it from time to time. This study used anthropological approach by utilizing the theory of Robert Redfield on the interaction of great tradition and little tradition. The results of this study indicate that although Reyog has interacted with various cultures, particularly Islam, it is able to reform and reformulate its tradition and find cultural attitudes flexible with various cultures that come with it. The cultural attitudes embody in stage-modernization, transformation of mythologies and reforms of the symbols of social values. Reyog sebagai seni pentas arak-arakan yang telah ada di Ponorogo semenjak pra-Islam masih berkembang hingga saat ini bahkan terus mengalami perkembangan ke luar daerah Ponorogo baik secara regional, nasional, dan internasional. Reyog pada masa sekarang secara umum diakui sebagai identitas budaya bangsa Indonesia. Kenyataan itu berbeda dengan tradisi Jawa lain yang telah runtuh dan tinggal dalam arkeologi sejarah budaya seperti kentrung, ludruk, dan ketoprak. Keadaan ini menimbulkan pertanyaan menarik tentang bagaimana Reyog bertahan dari gempuran berbagai budaya yang datang menyerangnya dari zaman ke zaman. Penelitian ini menggunakan pendekatan antropologi dengan memanfaatkan teori Robert Redfield tentang pertemuan tradisi besar (great tradition) dan budaya kecil (little tradition). Hasil penelitian ini menunjukkan bahwa meskipun Reyog bertemu dengan berbagai budaya, khususnya Islam, Reyog mampu mereformasi dan mereformulasi tradisinya sehingga ditemukan sikap budaya yang lentur dan cocok dengan berbagai budaya yang datang bersamanya. Sikap budaya itu berbentuk modernisasi pentas, transformasi mitologi, dan reformasi melalui simbol-simbol nilai sosial-kemasyarakatan.